Arabic Terms About Covid-19: Problems of Their Translation Into Indonesian and Sundanese Languages - Akmaliyah Akmaliyah; Mohammad Rosyid Ridho; Yasir Hudzaifah; Amiq Amiq; Zalifa Nuri (Dinasti International Journal of Education Management And Social Science, 2024)
The focus of this study is related to the translation techniques of Covid-19 terms from Arabic language into Indonesian language and one of its regional languages, Sundanese. The translation materials are the learning material texts submitted by students on WhatsApp. This study uses a comparative descriptive method to analyze the transformation of vocabularies or terms in Arabic into Indonesian and one its regional language, Sundanese. Regarding the texts, no different from any translation of other texts, the techniques used that can be observed here are pure borrowing or literal translation, naturalized borrowing, and established equivalent. The technique of pure borrowing seems to be done as the last resort; words, such as virus, corona, internet, soap and bacteria, are not terms familiar for everyday conversation in these languages. Even more, other words, such as frustrasi, depresi, ahli jiwa ‘frustration, depression, psychiatrist’, have no equivalents in Sundanese. Consequently, these words are not translated in Sundanese text, but taken as they are. Comparing the translation results from Arabic into Indonesian and Sundanese gives us information that very often to use the terms as used in the Indonesian language is the only option the Sundanese students might have.